Dynamic Assessment and second language development. (October 2021) - Poehner, Matthew E.; Wang, Zhaoyu
Abstract : This timeline is concerned with Dynamic Assessment (henceforth, DA) as it has been taken up and elaborated in contexts involving the teaching, learning, and assessment of learners of second languages (L2s). DA is distinguished by its insistence that an individual's independent performance of assessment tasks reveals only part of his/her abilities, namely those that have completed their development at the time of the assessment; insights into abilities that have begun to emerge but have not yet fully developed can be determined according to an individual's responsiveness to particular kinds of support, referred to as mediation (e.g., reminders, leading questions, hints, provision of a model, feedback), offered during the assessment as difficulties arise (Haywood & Lidz, 2006). In this respect, DA differs from more conventional distinctions in assessment, such as that between assessments concerned with the results of previous learning ('summative assessment') and those intended to provide information relevant to subsequent instruction ('formative assessment'). Instead, the embedding of an interactive, instructional element within the assessment procedure allows for the possibility of expanding the evidential basis upon which summative interpretations of learner abilities are made; that is, the results encompass previous learning that has resulted in both complete and partial understanding of relevant concepts. At the same time, DA serves a formative function in so far as interaction allows insights into the underlying sources of learner difficulties and the kind of support to which they are most responsive (Sternberg & Grigorenko, 2002).